1982
DOI: 10.1007/978-3-642-68511-8_46
|View full text |Cite
|
Sign up to set email alerts
|

Statistics and the LD50 Study

Abstract: Abstract. An increasing concern over the LDso study has become apparent over the years and even more so recently in Britain with the Home Office Publication on the subject and comments and opinions expressed in the National Press. Particularly with respect to the Pharmaceutical and Agrochemical Industries, the number of animals used depends on the number required to satisfy the Regulatory Authorities. Is there a scientific rationale for using the number of animals required? Data is presented justifying the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
5
0
Order By: Relevance
“…H the dose groups were committed in a sequential way, such that the result of the initial dose was taken into account in setting the rest, then 2 animals per group would be sufficient in most cases. Tattersall [30] reached a similar conclusion.…”
Section: ~~ ____ ~ __ ----------------------------------74%supporting
confidence: 52%
“…H the dose groups were committed in a sequential way, such that the result of the initial dose was taken into account in setting the rest, then 2 animals per group would be sufficient in most cases. Tattersall [30] reached a similar conclusion.…”
Section: ~~ ____ ~ __ ----------------------------------74%supporting
confidence: 52%
“…From the lively discussion going on in many scientific circles, societies and expert groups, it has become clear that much important information on the acute toxic hazards of chemicals can be obtained with small numbers of animals. It has also been shown that it is often not necesssary to use doses that cause mortality in a substantial number of the subjects (Tattersall, 1982). Other scientists have resumed the approaches of earlier workers (Deichmann and Le Blanc, 1943;Thompson, 1947;Deichmann and Mergard, 1948;Dixon and Mood, 1948;Weil, 1952;Brownlee et al 1953), and have demonstrated convincingly that it is possible to determine LDs0 values with satisfactory precision, using a total of 12 animals or less (Mueller and Kley, 1982;Schuetz and Fuchs, 1982;Lorke, 1983;Bruce, 1985).…”
Section: Current Notions and Controversiesmentioning
confidence: 99%
“…The scientific significance of the classical LDs0 test has been questioned on the basis of the relatively broad variability of the test results and for animal welfare reasons (Zbinden and Flury-Roversi 1981;Bass et al 1982;Tattersall 1982). For the evaluation of the acute oral toxicity of substances it is not necessary to derive this information with an LDs0 test using large numbers of animals but instead with the use of only few animals that are carefully monitored for signs of toxicity and signs of recovery or mortality.…”
Section: Introductionmentioning
confidence: 99%